MODERN FOREIGN CONSTITUTIONALISM: MAX PLANCK INSTITUTE FOR COMPARATIVE PUBLIC LAW AND INTERNATIONAL LAW - Mykhaylo O. Baymuratov; Natalia V. Bocharova (Alfred Nobel University Journal of Law)
The European vector of modern Ukrainian politics involves a broad and thorough acquaintance with the latest achievements of European and world legal thought. Domestic jurisprudence, which has been developing for many years in line with the orthodox Marxist methodology, overcomes not only ideological isolation, but also produces a new research culture based on the study and understanding of modern trends in foreign jurisprudence. It is necessary to emphasize that this process is only unfolding and is not always implemented in specific studies, in particular, dissertation studies, where the use of works by foreign authors on the studied issues is often absent, and, therefore, the latest methodological approaches and theoretical and doctrinal developments of the world's leading experts are not taken into account. As before, little information is published in domestic legal periodicals about foreign research centers and schools in various fields of law, activities of foreign legal scholars, academic publishing houses and authoritative periodicals. All this fully applies to our science of constitutional law, which encourages us to more actively cover the study of constitutional law in foreign countries, publishing activity and activities of scientific centers related to the problems of constitutional law. One of the internationally recognized centers of modern constitutional studies is the Max Planck Institute of Comparative Public Law and International Law (Heidelberg, Germany). His research in many respects sets the tone and determines the direction of modern constitutional and legal investigations. The article provides a detailed description of the work of the Institute, which is built on the principles of theoretical and methodological pluralism, individual projects are specifically directed to the use of different methodological approaches. It is noted that the research is conducted in two forms: 1) doctrinal and theoretical analysis - problem-oriented fundamental research that seeks to reveal the structures, development and regularities of constitutional and international law; 2) systematic analysis and comparison of legal norms in order to solve current legal problems or carry out reforms. The relatively low level of abstraction of such studies is explained by the need to provide specific recommendations to officials or practicing lawyers. The institute strives for broad relations with the public. It is noted that the Institute occupies a leading position in world constitutionalism in terms of the volume of research conducted, the wide coverage of topics and the depth of theoretical analysis. His achievements must be taken into account by the domestic science of constitutional law.